2006
DOI: 10.1055/s-2006-933115
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Strategy to Prepare Water-Soluble Prodrugs of Ketones

Abstract: A novel method for the synthesis of water-soluble ketoxime phosphate prodrugs avoiding the unwanted Beckmann rearrangement is developed. In the first step, a novel in situ prepared phosphorochloridic acid bis-(2-trimethylsilyl-ethyl) (TMSE) ester 1 reacts with the hydroxyimine 2. In the second step, the formed TMSE-phosphate triester 3 undergoes a tetrabutylammonium fluoride mediated microwave-assisted conversion into the corresponding ketoxime phosphate salt 4 without further Beckmann rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A series of oxime derivatives were prepared from 24 in order to add diversity to this chemical series and to probe SAR. The oxime functionality was desirable because it is already contained in known drugs and has shown activity against protozoa , and evidence suggests that it is a suitable “water-soluble prodrug” that might unveil the ketone under biological conditions. The initial series of analogues, prepared by treating 24 with the appropriate commercially available hydroxylamine in pyridine, consisted of the parent oxime ( 25 ), the O -methyloxime ( 26 ), and the O -allyloxime ( 27 , Scheme a). Analogues containing bulkier alkyl groups were also prepared and included cyclopropylmethylene oxime ( 28 ), isobutyloxime ( 29 ), and tert -butyloxime ( 30 ).…”
Section: Analogue Synthesismentioning
confidence: 99%
“…A series of oxime derivatives were prepared from 24 in order to add diversity to this chemical series and to probe SAR. The oxime functionality was desirable because it is already contained in known drugs and has shown activity against protozoa , and evidence suggests that it is a suitable “water-soluble prodrug” that might unveil the ketone under biological conditions. The initial series of analogues, prepared by treating 24 with the appropriate commercially available hydroxylamine in pyridine, consisted of the parent oxime ( 25 ), the O -methyloxime ( 26 ), and the O -allyloxime ( 27 , Scheme a). Analogues containing bulkier alkyl groups were also prepared and included cyclopropylmethylene oxime ( 28 ), isobutyloxime ( 29 ), and tert -butyloxime ( 30 ).…”
Section: Analogue Synthesismentioning
confidence: 99%
“…4 Recently a study of ketoxime phosphates using as phosphate prodrug structures has been reported. 5 Therefore the development of a facile and efficient method for synthesis of the oxime phosphates is required.…”
mentioning
confidence: 99%